New Native Neuropteroid Insects - Nathan Banks (Psyche: A Journal of Entomology)
The following few descriptions are based on materials gradually accumulating in the Museum of Comparative Zoology. A generic synopsis of our Capniinae, including two new genera, is based on characters that, I believe, are better than those previously used in this group.